2018
DOI: 10.1177/0954405418755827
|View full text |Cite
|
Sign up to set email alerts
|

Research on machining topography of point grinding based on correlation function method

Abstract: Point grinding uses the point contact to shape surface topography of workpiece which has high machining precision. Its surface topography has a close relation with its service performance. In order to study the topography of point grinding, these authors carried out the experiment and established a new assessing model based on the correlation function method. The inner characteristics of topography are revealed by self-correlation and mutual correlation function method and its mechanism is analyzed. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They move together between the grinding wheel and the workpiece during grinding process. 23,24 This type of ground scratch can be controlled by selecting the grinding wheel with proper characteristics and cleaning the surface of grinding wheel. Another kind of scratch is shown in Figure 16(b).…”
Section: Surface Scratchmentioning
confidence: 99%
“…They move together between the grinding wheel and the workpiece during grinding process. 23,24 This type of ground scratch can be controlled by selecting the grinding wheel with proper characteristics and cleaning the surface of grinding wheel. Another kind of scratch is shown in Figure 16(b).…”
Section: Surface Scratchmentioning
confidence: 99%
“…For example, amplitude distribution function is commonly used to describe the probability distribution of surface micro height and characterize the geometrical features, 21,22 while bearing area curve as a statistical function has a superior performance in assessing the wear resistance, load bearing, and lubricant or oil retention capacity of the machined surface. 23,24 Shi et al 25 revealed the inner characteristics of surface topography obtained by point grinding based on self-correlation and mutual correlation function. Furthermore, 3D amplitude and functional parameters belong to time-dominant quantification parameters, which cannot explain the dynamic frequency information of the machined surface.…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of crank journal outer circle accuracy has an important impact on the stable operation performance of crankshaft [1,2]. Grinding factors such as the dynamic unbalance, the rotation accuracy and the clamping error directly affect the accuracy consistency [3,4]. How to maximize the accuracy consistency of the outer circle of the crank journal is the key to the high motion accuracy and good interchangeability of the crankshaft.…”
Section: Introductionmentioning
confidence: 99%